UMLCollab: Uma abordagem híbrida para modelagem colaborativa de modelos UML - Xavier, McLyndon S. de L.; Farias, Kleinner; Barbosa, Jorge; Gonçales, Lucian; Bishoff, Vinicius (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2019)
In collaborative software modeling the two main types of collaboration still present problems, such as the constant interruptions that hinder the cognitive process in synchronous collaboration, and the complicated and costly stages of conflict resolution in asynchronous collaboration. For this, this paper proposes a technique called "UMLCollab". This technique combines aspects from synchronous and asynchronous collaboration. Through experiments, developers applied the proposed solution and they achieved to an intermediate productivity in relation to traditional collaboration methods. The results showed that the "UMLCollab" improved the correctness of the changed models, the notion of developer regarding to the resolution of conflicts, and enabled the parallel changes occurring while other collaborators are working on without degrade the software diagrams being modelled locally.